2021
DOI: 10.1080/21655979.2021.1947167
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regulatory effect of miR-149-5p on Sphingosine-1-phosphate receptor 2 of pericytes and its neuroprotective molecular mechanism after acute cerebral ischemia reperfusion in rats

Abstract: To investigate the effect of miR-149-5p on sphingosine-1-phosphate receptor 2 (S1PR2) expression level and contents of matrix metalloproteinase (MMP-9) and superoxide dismutase (SOD) in the pericytes after acute cerebral ischemia reperfusion in rats, so as to clarify the neuroprotective molecular mechanism induced by miR-149-5p and provide references for the treatment of neurological diseases, 60 male SD rats aged 7-8 weeks were selected and divided randomly into test group (establishing middle cerebral artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For instance, in cerebral ischemia, MMP expression is increased, and they are a target of miR-149-5p so that in the middle cerebral artery occlusion (MCAO) model, the use of miR-149-5p mimic can reduce the extent of neurological defects and tissue damage by decreasing the level of MMP2 and MMP9 [22] . Another study demonstrated that in the MCAO model, miR-149-5p significantly decreased the expression of MMP9 [23] . In U251 GBM cells, overexpression of miR-149 inhibits expression of MMP2, thereby suppressing proliferation and invasion of GBM via AKT1 signaling; however, in this work, no distinction is made between both strands of miRNA-149 [24] .…”
Section: Discussionmentioning
confidence: 96%
“…For instance, in cerebral ischemia, MMP expression is increased, and they are a target of miR-149-5p so that in the middle cerebral artery occlusion (MCAO) model, the use of miR-149-5p mimic can reduce the extent of neurological defects and tissue damage by decreasing the level of MMP2 and MMP9 [22] . Another study demonstrated that in the MCAO model, miR-149-5p significantly decreased the expression of MMP9 [23] . In U251 GBM cells, overexpression of miR-149 inhibits expression of MMP2, thereby suppressing proliferation and invasion of GBM via AKT1 signaling; however, in this work, no distinction is made between both strands of miRNA-149 [24] .…”
Section: Discussionmentioning
confidence: 96%
“…Sections were viewed under a confocal microscope (Olympus, Tokyo, Japan) (200x). Spinal cord tissues from each rat were randomly stained in three tissue sections, with five randomly chosen fields of view photographed in each section [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In rat pericytes after MCAO, miR149-5p increased expression of sphingosine-1-phosphate receptor 2 (S1PR2), superoxide dismutase (SOD) 1-3 and significantly decreased the expression of MMP9, thereby alleviating BBB permeability and playing a protective role for neurons (Yan et al, 2021). Furthermore, ICV injection of antagomir-149-5p attenuated BBB permeability and improved MCAO outcomes in rats (Wan et al, 2018).…”
Section: The Effect Of Mirna On Bbb Dysfunctionmentioning
confidence: 99%